1987
DOI: 10.3109/00016348709103655
|View full text |Cite
|
Sign up to set email alerts
|

C‐Reactive Protein: An Early Marker for Neonatal Bacterial Infection Due to Prolonged Rupture of Amniotic Membranes And/Or Amnionitis

Abstract: The C-reactive protein (CRP) concentration was determined in 25 infants whose mothers had presented with prolonged rupture of amniotic membranes (PROM) and/or amnionitis. CRP was positive (i.e. greater than or equal to 6 mg/l) within the first 6 hrs of life in 10 and negative in 15 infants. Clinically, all infants with positive CRP developed symptoms suggesting bacterial infection and both the absolute immature neutrophil counts as well as the ratio immature/total neutrophils were significantly higher in them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

1990
1990
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 5 publications
0
4
0
2
Order By: Relevance
“…from these risk factors, it is thought that measuring C-reactive protein (CRP) and/or white blood cells (leukocytes) might be of value for early detection of neonatal infection in these patients. 5,6 In the literature, conflicting results on the use of CRP in the prediction of infection in women with PROM have been reported. [5][6][7] In 2007, Trochez-Martinez et al performed a systematic review and found no clear evidence that supported the use of CRP for the early diagnosis of chorioamnionitis.…”
mentioning
confidence: 99%
“…from these risk factors, it is thought that measuring C-reactive protein (CRP) and/or white blood cells (leukocytes) might be of value for early detection of neonatal infection in these patients. 5,6 In the literature, conflicting results on the use of CRP in the prediction of infection in women with PROM have been reported. [5][6][7] In 2007, Trochez-Martinez et al performed a systematic review and found no clear evidence that supported the use of CRP for the early diagnosis of chorioamnionitis.…”
mentioning
confidence: 99%
“…The "low values protocol" (calibration range: 0.003-0.050 g/L) permits the measurement of moderately increased CRP concentrations and, at the same time, a great part of normal concentrations in sera from healthy adults (7,16). It can be useful to monitor declining or latent inflammatory reaction (27)(28)(29) or to detect, at the earliest possible moment, an infection in neonate children (30,31) by using a small volume of serum (great sample dilution). Because of the sensitivity of the method, it may be also possible to consider the application of a modified protocol using a lower sample dilution, suitable for other biological fluids with low CRP concentrations, such as synovial fluid (32) in rheumatic disorders, cerebrospinal fluid (CSF) in bacterial and viral meningitis (33)(34), or cord blood serum (17).…”
Section: Discussionmentioning
confidence: 99%
“…Neste estudo, utilizamos o teste de aglutinação do látex semiquantitativo por ser de fácil execução. Baseamo-nos no trabalho de Salzer et al 44 , no qual esse método foi utilizado em casuística semelhante à nossa ou, seja, em RNs com fatores de risco para infecção neonatal precoce. …”
Section: Indicadores Imunológicos Nas Infecções Neonataisunclassified
“…Em nossa casuística, todos os RNs tinham pelo menos um fator de risco para infecção e, entre os 18 que se tornaram sintomáticos, 11 deles tinham mais do que um fator de risco associado (tabela 1), fato que nos leva a crer que o estímulo para a produção de proteína C-reativa, através das interleucinas, possa ter ocorrido antes do nascimento. Essa hipótese está de acordo com o estudo de Salzer et al 44 , no qual os autores observaram que de 25 RNs, cujas mães tinham RPM e/ou amnionite clínica, dez apresentaram positividade para proteína C-reativa pelo teste de aglutinação do látex, com seis horas de vida, e todos estes mostraram sintomatologia infecciosa posterior.…”
Section: Proteína C-reativa Ao Nascimentounclassified